Calcification and airway stenosis in a child with chondrodysplasia calcificans punctata - Goussard, Pierre (BMJ Publishing Group, 2014)
Calcification of the airways is rarely seen in children. A male baby was born at 34 weeks with severe respiratory distress. Intubation was difficult with severe hypercarbia after intubation. Chest radiography demonstrated calcification in the tracheobronchial tree and this was confirmed with Chest CT scan. Flexible bronchoscopy confirmed long-segment funnel tracheal stenosis with visible calcifications in the trachea and bronchi. Chondrodysplasia punctata was diagnosed based on the clinical and radiological findings.